KEABSAHAN PERKAWINAN BEDA AGAMA MENURUT HUKUM NASIONAL - Daffa Arya Yuanasari (2022)
Marriage is an officially regulated and sacred thing. Indonesia regulates marriage in the Marriage Law. Basically, the Marriage Law does not explain the definition of interfaith marriage. However, the practice of interfaith marriages in Indonesia is still common. Interfaith marriage itself is actually prohibited in Article 2 paragraph (1) of the Marriage Law. However, there are still many people who carry out interfaith marriages, on the grounds that there is a legal vacuum in the Marriage Law. The practice of interfaith marriages is carried out by many artists, which attracts public attention because it is carried out by several pairs of public figures. The purpose of this study is to determine the validity of interfaith marriages according to national law and to find out the legal consequences of interfaith marriages. This research uses normative legal research (normative juridical), which in turn uses a statutory approach. The results of this study indicate that interfaith marriages carried out in Indonesia when viewed from the national law are invalid because they violate Article 2 paragraph (1) of the Marriage Law no. 1 of 1974 concerning Marriage. Almost every religious teaching is not allowed to carry out interfaith marriages. This practice can result in the legal status and position of the child born from the marriage. Because interfaith marriages are legally considered invalid. So, the child born from the marriage is not the heir of the biological father.